Analisis Risiko dengan Pendekatan Semi-Kuantitatif untuk Stabilitas Lereng Highwall pada PIT B1 PT. Pancaran Surya Abadi Kabupaten Kutai Kartenegara - Melki Marten; Revia Oktaviani; Windhu Nugroho; Tommy Trides; Albertus Juvensius Pontus (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Guaranteeing the geotechnical stability of slopes is an absolute prerequisite for the sustainability of open pit mining operations, considering the potential for multidimensional losses due to slope failure. The specific geological conditions at PIT B1 PT. Pancaran Surya Abadi, which is composed of sedimentary rocks (coal, sandstone, and claystone), are susceptible to degradation and softening, especially due to high rainfall that causes an increase in pore water pressure and a decrease in rock shear strength. This study aims to analyze the stability of highwall slopes using the Morgenstern-Price Method to determine the Safety Factor (SFF) value according to Ministerial Decree number 1827 K/30/MEM/2018, and continued with a semi-quantitative risk analysis. The analysis results show that the initial slope has a static SFF of 0.77 (Not Safe). After redesign, the recommended optimal single slope geometry is: sandstone (Height 5 m, Angle 20°, Berm 5 m) and claystone (Height 10 m, Angle 60°, Berm 5 m). This redesign resulted in a FK of 1.34 (Safe). Sensitivity analysis to groundwater level rise (GTL) showed that the GTL value remained safe (GTL ≥1.30) up to a 30% increase in GTL. However, a 40% to 80% increase in GTL caused the GTL to decrease (1.28–1.21), classified as Medium Risk. A 100% increase in GTL drastically reduced the GTL to 1.05, classified as High Risk. This study emphasizes the need for close monitoring and additional drainage to maintain the long-term stability of slopes under the influence of rainfall.